Knowledge, attitudes, behavior, and self-efficacy related to evidence-based practice among healthcare professionals working in the municipal healthcare service in Norway: a cross-sectional survey - Nils Gunnar Landsverk; Nina Rydland Olsen; Therese Brovold (BMC, 2024)
Abstract Background Practicing the process of evidence-based practice (EBP) may be challenging for healthcare professionals and may be affected by their EBP knowledge, attitudes, self-efficacy, and behavior. We have some insight into how Norwegian healthcare professionals and students perceive EBP. However, research on the perception of EBP among primary healthcare professionals working in the Norwegian municipal health service is lacking. This study aimed to map EBP knowledge, attitudes, behavior, and self-efficacy among healthcare professionals working with older people in the municipal health service in Norway and to examine associations between how they score and their background characteristics. Methods A cross-sectional web-based survey was conducted among healthcare professionals in the Norwegian municipal healthcare service. We used the revised Norwegian version of the Evidence-based practice profile questionnaire (EBP2-N) to measure the healthcare professionals' EBP knowledge, attitudes, behavior, and self-efficacy, operationalized through the five domains of the EBP2-N. We calculated the mean scores for each EBP domain across the total sample and for each subgroup of healthcare professionals. We used a one-way between-groups analysis of variance (ANOVA) to analyze the differences in mean scores between the professions. We also calculated eta-squared values to determine effect size. We used linear regression analyses to examine associations with background variables. Results A total of 313 healthcare professionals, including nurses, assistant nurses, physical therapists, occupational therapists, and medical doctors, responded to the survey. The total sample scored the highest on the relevance domain, with a mean domain score of 58.9 (95% CI = 58.1-59.7) on a scale ranging from 14 to 70. The practice domain had the lowest score, with a mean domain score of 22.2 (95% CI = 20.8-21.6) on a scale ranging from 9 to 45. Statistically significant differences in mean scores were found between professions in all domains except the confidence domain. The most considerable differences between professions' mean scores were found for the relevance and terminology domains, with eta-squared values of 0.13 and 0.19, respectively. The multivariate regression results showed that EBP training was significantly associated with the sum score of the relevance, terminology, and confidence domain. However, EBP training was not associated with the sum score of the practice and sympathy domains. Conclusions Primary healthcare professionals in the Norwegian municipal healthcare service hold positive attitudes toward EBP. However, they report a low understanding of research terms, low self-efficacy in performing EBP activities, a lack of perceived compatibility of EBP with professional work, and a low frequency of EBP behavior. Additionally, we observed differences among the included professions in four out of five domains, suggesting that various professions may be unequally prepared for EBP. Finally, our results indicate potential positive outcomes of EBP training. Those who received EBP training exhibited more positive attitudes, a better understanding of common research terms, and higher self-efficacy in performing EBP activities. However, EBP training was not associated with their self-reported EBP behavior. Trial registration Retrospectively registered (prior to data analysis) in OSF Preregistration. Registration DOI: https://doi.org/10.17605/OSF.IO/428RP .